Signifikansi Surat Wasiat dalam Budaya Komunitas Kulit Putih Amerika bagian Selatan - Tatit Hariyanti (Humaniora, 2012)
This paper aims at revealing that last will and testament in southern white culture does not limit its function as the legal document for transfering material and worldly property as it has recently been the focus of some researchers and the belief of the majority of modern southerners. Southern last will and testament is a symbolic construct. Individually it is the representation or the self expression of the intention of the makers. Southern last will and testament is the expression of individual freedom to give or not to give his property to others and to keep or to reveal their hidden secret to public in the intention of preserving their honor. It is also utilized to embed familial and religious values.